2017
DOI: 10.4049/jimmunol.1601560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antiretroviral Therapy on the Memory and Activation Profiles of B Cells in HIV-Infected African Women

Abstract: HIV infection induces a wide range of effects in B cells, including skewed memory cell differentiation, compromised B cell function and hypergammaglobulinaemia. However, data on the extent to which these B cell abnormalities can be reversed by antiretroviral therapy (ART) are limited. To investigate the effect of ART on B cells, the activation (CD86) and differentiation (IgD, CD27 and CD38) profiles of B cells were measured longitudinally in 19 HIV-infected individuals before (median, 2 months) and after ART i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 75 publications
5
14
0
Order By: Relevance
“…Restoration of memory B cell responses in progressors post ART in this study is in agreement with previous studies documenting the beneficial effect of early initiation of ART ( 23 , 44 , 56 58 ). In 2013, WHO conditionally recommended that all 2- to 5-year-old HIV-1-infected children be placed on HAART, based on studies that demonstrated improvement in clinical and virological parameters post ART ( 52 ).…”
Section: Discussionsupporting
confidence: 93%
“…Restoration of memory B cell responses in progressors post ART in this study is in agreement with previous studies documenting the beneficial effect of early initiation of ART ( 23 , 44 , 56 58 ). In 2013, WHO conditionally recommended that all 2- to 5-year-old HIV-1-infected children be placed on HAART, based on studies that demonstrated improvement in clinical and virological parameters post ART ( 52 ).…”
Section: Discussionsupporting
confidence: 93%
“…Again IgG2 levels did not change with ART, remaining at the pre-therapy levels. In agreement with others (Tanko et al, 2017), it was found that the persistence of IgG disorders was not associated with the viral load (undetectable in all women). Indexes of immune activation were not measured in the study women, but it is likely that the persistence of inflammatory cytokines, a hallmark of HIV-induced immune activation status (Brenchley et al, 2006;Mehraj et al, 2019), could have affected IgG isotype switching (Tangye et al, 2002) and subclass synthesis (Kawano et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…It was also found that the high levels of total IgG and IgG1 were not associated with the viral burden, but rather with the CD4+ cell count, suggesting that the T-cell dysfunction could be the primary force leading to the general dysregulation of the immune system (Malaspina et al, 2003). These results are in agreement with those of previous studies that have found IgG abnormalities associated with markers of immunoactivation and to the decline in T-cell functionality (Abudulai et al, 2016D'Orsogna et al, 2007Tanko et al, 2017). The IgG isotype distribution was dominated by IgG1, which represented more than 90% of total IgG, followed by IgG3 (5.3%), while the IgG2 isotype, which accounts for 20-30% of total IgG in the normal population (Vidarsson et al, 2014;Puissant-Lubrano et al, 2015), accounted for only 5.2%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To date, there are no reports describing immune responses to SARS-CoV-2 in individuals infected with HIV-1. It is possible that individuals with HIV-1 may have incomplete immune reconstitution and impaired immunity that may influence vaccine safety and efficacy, even if they are receiving antiretroviral therapy, owing to persistent immune activation and incomplete recovery of T cell and B cell immunity 123,124 . Suboptimal neutralizing antibody responses have been described following immunization against influenza virus or other pathogens in individuals infected with HIV-1 (ref.…”
Section: Vaccine Platforms and Implementationmentioning
confidence: 99%